Physics and dance - Coates, Emily; Demers, Sarah (Yale University Press, 2019)
A fascinating exploration of our reality through the eyes of a physicist and a dancer--and an engaging introduction to both disciplines. From stepping out of our beds each morning to admiring the stars at night, we live in a world of motion, energy, space, and time. How do we understand the phenomena that shape our experience? How do we make sense of our physical realities? Two guides--a former member of New York City Ballet, Emily Coates, and a CERN particle physicist, Sarah Demers--show us how their respective disciplines can help us to understand both the quotidian and the deepest questions about the universe. Requiring no previous knowledge of dance or physics, this introduction covers the fundamentals while revealing how a dialogue between art and science can enrich our appreciation of both. Readers will come away with a broad cultural knowledge of Newtonian to quantum mechanics and classical to contemporary dance. Including problem sets and choreographic exercises to solidify understanding, this book will be of interest to anyone curious about physics or dance.